Things We Do for No Reason™: Routine Thyroid‐Stimulating Hormone Testing in the Hospital. Issue 9 (19th February 2020) - Wootton, Taylor; Bates, Ruth
Abstract : Inspired by the ABIM Foundation's Choosing Wisely ® campaign, the "Things We Do for No Reason ™ " (TWDFNR) series reviews practices that have become common parts of hospital care but may provide little value to our patients. Practices reviewed in the TWDFNR series do not represent "black and white" conclusions or clinical practice standards but are meant as a starting place for research and active discussions among hospitalists and patients. We invite you to be part of that discussion . Abstract :